2010
DOI: 10.1007/s10342-010-0443-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen budgeting and quality of exponentially fertilized Quercus robur seedlings in Ireland

Abstract: Current policy in Ireland calls for increased quality and quantity of broadleaved seedling plantings. Simultaneously, concerns regarding environmental contamination necessitate development of nursery production methods that minimize impacts. Exponential (E) fertilization has potential for producing high-quality seedlings through nutrient loading, while simultaneously minimizing nitrogen (N) losses during culture. We investigated the effects of a wide range (0.10-1.0 g N seedling -1 year -1 ) of E fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…First, increasing N availability shifts allocation patterns of current photosynthetic products to aboveground organs (Hernández et al 2009). This pattern has been observed in bareroot experiments with other Quercus species, leading to a plateau of root biomass in the absence of toxicity (Salifu et al 2009a;Schmal et al 2010). Second, the confinement effect of container size precludes the potential expression of root growth.…”
Section: Discussionmentioning
confidence: 85%
“…First, increasing N availability shifts allocation patterns of current photosynthetic products to aboveground organs (Hernández et al 2009). This pattern has been observed in bareroot experiments with other Quercus species, leading to a plateau of root biomass in the absence of toxicity (Salifu et al 2009a;Schmal et al 2010). Second, the confinement effect of container size precludes the potential expression of root growth.…”
Section: Discussionmentioning
confidence: 85%
“…The noteworthy results of both Air-pots proved that the larger volume size was effective in increasing: (a) the duration of the growing season through early October, which is an advantage in Mediterranean conditions where early frosts are uncommon; (b) the growth rate of seedlings, and thus (c) their final height and biomass. One-year-old seedlings in Air-pots were much taller than those observed in traditional and common container types for both species at the same age (Johnson 1981;Aldhous and Mason 1994;Brønnum 2004;Schmal et al 2011). Chirino et al (2008 observed that deeper containers (30 cm) produced taller seedlings in Q. suber.…”
Section: Nursery Trialmentioning
confidence: 96%
“…A pesar de que diversos estudios en latifolias, entre los que destacan los realizados por Close et al (2005) y Schmal et al (2011) demuestran que la técnica o régimen de fertilización exponencial es una práctica que no solo favorece un crecimiento superior, sino que también promueve la acumulación de reservas nutrimentales, en este estudio no ocurrió de esta manera. De acuerdo con los resultados, en plantas de E. cyclocarpum, el suministro de nutrimentos en forma exponencial no promueve características que podrían ser adecuadas para que las plantas se desempeñen satisfactoriamente en sitios competitivos.…”
Section: Régimen De Fertilizaciónunclassified